Color-selective photophobia in ictal vs interictal migraineurs and in healthy controls. Issue 10 (October 2018) - Nir, Rony-Reuven; Lee, Alice J.; Huntington, Shaelah; Noseda, Rodrigo; Bernstein, Carolyn A.; Fulton, Anne B.; Bertisch, Suzanne M.; Hovaguimian, Alexandra; Buettner, Catherine; Borsook, David; Burstein, Rami
Abstract : Abstract: Aversion to light is common among migraineurs undergoing acute attacks. Using psychophysical assessments in patients with episodic migraine, we reported that white, blue, amber, and red lights exacerbate migraine headache in a significantly larger percentage of patients and to a greater extent compared with green light. This study aimed at determining whether these findings are phase-dependent–namely, manifested exclusively during migraine (ictally) but not in its absence (interictally), or condition-dependent—ie, expressed uniquely in migraineurs but not in healthy controls. To determine whether the color preference of migraine-type photophobia is phase- or condition-dependent, we compared the effects of each color of light in each intensity between migraineurs during and in-between attacks and healthy controls. During the ictal and interictal phases, the proportion of migraineurs reporting changes in headache severity when exposed to the different colors of light increased in accordance with elevated light intensities. During the ictal phase, white, blue, amber, and red lights exacerbated headaches in ∼80% of the patients; however, during the interictal phase, light initiated headache in only 16% to 19%. Notably, green light exacerbated headaches in 40% and triggered headaches in 3% of the patients studied during the ictal and interictal phases, respectively. With one exception (highest red light intensity), no control subject reported headache in response to the light stimuli. These findings suggest that color preference is unique to migraineurs—as it was not found in control subjects—and that it is independent of whether or not the patients are in their ictal or interictal phase. Abstract : Migraineurs prefer green light because it hurts them less than other colors during migraine and is less likely to trigger a headache in between attacks.